The Urgency of Sharia Compliance in the Islamic Economic System in Indonesia - Willy Sandy (Department of Sharia Economic Law, 2026)
This study examines the urgency of sharia compliance as a foundational element in strengthening the credibility, sustainability, and public trust in Islamic economic institutions in Indonesia. Sharia compliance is not merely a formal legal requirement but serves as a normative and strategic instrument rooted in the principles of maqāṣid al-syarī‘ah, emphasizing justice, transparency, accountability, and the protection of wealth and public welfare. The research highlights the central role of the National Sharia Council–Indonesian Ulema Council (DSN-MUI) in issuing fatwas that guide the operational practices of Islamic financial institutions, as well as the importance of harmonizing these fatwas with national regulations issued by the Financial Services Authority (OJK) and Bank Indonesia. The findings reveal several challenges in aligning DSN-MUI fatwas with state regulation, including normative dualism between Islamic law and positive law, structural differences in institutional priorities, and practical limitations within Islamic financial institutions in implementing fatwa-based governance. These challenges contribute to regulatory gaps and inconsistencies that may undermine the integrity of Islamic finance operations. The study emphasizes the need for strengthening sharia governance through empowering Sharia Supervisory Boards (DPS), enhancing institutional capacity, improving regulatory integration, and utilizing digital technologies for transparent and efficient sharia supervision. Furthermore, the research underscores that effective harmonization between fatwas and state regulations requires continuous collaboration among DSN-MUI, OJK, BI, policymakers, and academia. The study concludes that sharia compliance is essential not only for institutional legitimacy but also for achieving the broader goals of Islamic economics, such as justice, welfare, and economic empowerment. Ultimately, sharia compliance should be understood as a comprehensive normative and regulatory framework that ensures the competitiveness and sustainability of Indonesia’s Islamic financial system in both national and global contexts.